Inventário de movimentos de massa do município de Castelo, Espírito Santo - Nunes, Daiane Ribeiro (2023)
This study aims to create an inventory and analyze the spatiality and temporality of mass movements data that occurred in the municipality of Castelo, Espírito Santo, contributing to guide future planning actions to mitigate or reduce the incidence of this type of event. In order to carry out this work, it was decided to use the traditional method of inventory, through analysis of historical and journalistic archives, scientific publications, technical reports and decrees of Municipal and State Civil Defense and identification in the field with photographic records of the areas of scars from the mass movements that occurred in the municipality from 1983 to 2022. Among the conditioning agents identified in this study, we can point out some examples that led to the outbreak of mass movements. Accumulated rainfall was related to about 84% of landslide events; 82.3% of the events occurred on slopes above 20 to 45%, of the strong wavy relief, 98.7% of the occurrences are located in the geomorphological units of Massifs of Caparaó I and II, characterized by an intensely dissected pattern; 61.9% occurred close to a sinistral transcurrent fault and/or structural lineaments: surface traces S. 61, 9% of the events, 49.7% corresponded to planar landslides and 12.2% corresponded to falling blocks: rolling . 38.1% of the recorded mass movements did not occur close to lineaments demarcated in the aforementioned scale. As for hypsometry, it was found that 59.5% of the events vary at altitudes from 100 to 300m, 14.2% at altitudes from 300 to 500m, 11.9% at altitudes from 500 to 700m and 14.2% of the events range in altitudes from 700 to 900m. 79% occurred in areas that underwent anthropic modifications, 66% were in urban areas, evidencing the lack of territorial planning for occupation and urban expansion.